Conspecific and predator perception of the Red Oophaga pumilio Morph from the Central Caribbean of Costa Rica - Chaves Acuña, Wagner (2020)
Strawberry Poison Frogs (Oophaga pumilio) are common members of leaf litter lowland communities in Central America and exhibit several color morphs throughout their distribution. Color plays a determinant role during intra- and intermorph interactions in many insular populations, but little is known about the variation and perception of visual signals in mainland populations. In this study, we investigated color variation of four body parts—head, back, belly, and throat—in a bright red O. pumilio population of northeastern Costa Rica. We incorporated frog- and bird-specific visual modeling to evaluate the differences in color and brightness between the sexes, from the perspective of conspecifics and avian predators. Furthermore, we measured the color and brightness contrast against natural backgrounds commonly used by these frogs to forage and patrol within territories. Our results revealed that, from the perspective of conspecifics, there is no dichromatism between males and females. However, females had a greater contrast against green and brown backgrounds than males. The bird visual models indicated that males and females are highly conspicuous against common background substrates but that females are easier to detect than males. This study detailing color variants between sexes within a mainland population of O. pumilio contributes to our understanding of color differences in populations of this species.